Meningkatkan Pemahaman Operasi Penjumlahan Melalui Metode Latihan (Drill) Pada Siswa Kelas III SDN Banyuajuh 4 - Rahma Nisa'ul Aulia; Ananda Nailatus Saadah; Allia Ayu Derajati; Machful Indrakurniawan (Yayasan Citra Dharma Cindekia, 2026)
This study was designed to optimize students' understanding of addition operations through the application of the drill method to third-grade students at SDN Banyuajuh 4. The primary problem underlying this study was students' weak mastery of addition concepts, particularly in the use of the storing technique, as reflected in numerous errors and low grades. The approach used in thisI study was Classroom Action Research (CAR) using the Kemmis and McTaggart model, which encompasses four main stages: planning, action, observation, and reflection. The study was conducted in two cycles involving 10 students. Data were collected throughIobservation, interviews,Itests, and documentation. Data were thenIanalyzed descriptively using quantitative and qualitative approaches, including calculating average grades and learning completion levels. The research findings showed a consistent increase in students' understanding across each cycle. The average score in the pre-cycle was 62.5, with 10% completion. This increased to 72.5 in the first cycle, with 50% completion. In the second cycle, it reached an average of 81.5, with 100% completion. Furthermore, student engagement in the learning process also increased significantly. Thus, the drill method has proven to be an effective solution for improving understanding of addition operations and encouraging improved learning outcomes and active student participation.